Discrimination of Biomechanically Possible and Impossible Hand Movements at Birth. Issue 2 (1st December 2014) - Longhi, Elena; Senna, Irene; Bolognini, Nadia; Bulf, Hermann; Tagliabue, Paolo; Macchi Cassia, Viola; Turati, Chiara
Abstract : The development of human body perception has long been investigated, but little is known about its early origins. This study focused on how a body part highly relevant to the human species, namely the hand, is perceived a few days after birth. Using a preferential‐looking paradigm, 24‐ to 48‐hr‐old newborns watched biomechanically possible and impossible dynamic hand gestures (Experiment 1, N  = 15) and static hand postures (Experiment 2, N  = 15). In Experiment 1, newborns looked longer at the impossible, compared to the possible, hand movement, whereas in Experiment 2 no visual preference emerged. These findings suggest that early in life the representation of the human body may be shaped by sensory‐motor experience.